2007
DOI: 10.1177/1473325007074164
|View full text |Cite
|
Sign up to set email alerts
|

Finding A Place in the World: The Experience of Recovery from Severe Mental Illness

Abstract: This hermeneutic phenomenological study of 45 adults with serious and persistent mental illness (SPMI) examines the experience of recovery over 3 years. After a brief review of the results from the first two phases, this article reports the findings from the third phase of the recovery process. Five essential themes are identified: (1) reintegration in the community; (2) reintegration with family and friends; (3) reintegration with the case manager; (4) reintegration with oneself; (5) barriers to social inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 22 publications
(22 reference statements)
4
59
0
2
Order By: Relevance
“…This result is similar to the findings of the previous study conducted by Strack and colleagues (2007). As for life purpose, people with SMI place importance on having meaningful lives, and individuals with SMI may lead meaningful lives despite the presence of psychiatric symptoms (Bradshaw, Armour, & Roseborough, 2007;Roe, Rudnick, & Gill, 2007;Spaniol et al, 2005). The results of the current study suggest that empowerment is significantly related to the presence of meaning in one's life, and are consistent with the literature supporting the importance of the consumer-oriented view of recovery (Davidson et al, 2005;Linhorst & Eckert, 2003;Markowitz, 2001;Noordsy et al, 2002;Spaniol et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to the findings of the previous study conducted by Strack and colleagues (2007). As for life purpose, people with SMI place importance on having meaningful lives, and individuals with SMI may lead meaningful lives despite the presence of psychiatric symptoms (Bradshaw, Armour, & Roseborough, 2007;Roe, Rudnick, & Gill, 2007;Spaniol et al, 2005). The results of the current study suggest that empowerment is significantly related to the presence of meaning in one's life, and are consistent with the literature supporting the importance of the consumer-oriented view of recovery (Davidson et al, 2005;Linhorst & Eckert, 2003;Markowitz, 2001;Noordsy et al, 2002;Spaniol et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…10,35,46 One study 44 reported that participants had "a longing for connection," p 328 while another study 26 witnessed social relationships as a decisive factor in recovery. One study 32 noted the importance of "being known, understood and accepted," p 4 while another identified the importance of supportive people.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…[30][31][32][33][34][35] Housing is one arena in which the deployment of such agency is vital. Numerous qualitative studies suggest that safe and secure housing is considered pivotal to recovery by people with mental illness, especially when they have exercised choice over type and location.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Numerosas investigaciones señalan la debilidad de las redes como uno de los principales problemas de la experiencia de la enfermedad mental, y cómo la vida laboral ayuda a paliarlo (Bradshaw, Armour, & Roseborough, 2007). Todos los participantes las reconocieron como partes transversales de la experiencia laboral.…”
unclassified